NAMING AND AFFECT. ONTOLOGICAL FUNCTION OF IDEOLOGY IN THE SCHOOL OF ESSEX’S DISCOURSE THEORY - Smoczynski, Rafal (Educação e Filosofia, 2011)
* Pesquisador da Academia Polonesa de Ciências, Varsóvia, Polônia. Naming and Affect. Ontological Function of Ideolog y in the School of Esse x’s Discourse Theor y Abstract: This paper maps the ontological function of affect and performativity as articulated in the School of Essex’s discourse theory, most notably in Ernesto Laclau and Chantal Mouffe’s writings. Firstly, it will be demonstrated that isolated agency of ideological performativity, does not involve sufficient power to introduce a coherent ontological consistency of both subject and object. Only the intertwine of libidinal force with naming, as the recent development of the School of Essex theory suggests, provides the sufficient conditions of the possibility of generating solid social ontology. Keywords: Laclau. Mouffe. Affect. Performativity. Social ontology. Hegemony. Bibliography: ALTHUSSER , L. For Marx. London: Allen Lane, 1969. _________ Ideology and Ideological State Apparatuses (Notes towards an Investigation)", in: Å½iÅ¾ek, S. (Org.) Mapping Ideology, London, 1994. Butler, J. Bodies that Matter: On the Discursive Limits of Sex, New York: Routledge, 1993. DERRIDA, J. Politiques de l’amitié, Paris: Galilée, 1994. _______. Acts of Religion. New York: Routledge, 2001. _______. Wiara i wiedza, In: Derrida , J.; Vattimo , G. (Org.). Religia. Warszawa: Wydawnictwo KR, 1999. FINK, B. The Lacanian Subject: Between Language and Jouissance, New Jersey: Princeton University Press, 1995. FREUD, S. Psychologia zbiorowoÅ›ci i analiza Ja. In: Reszke , R. (Org.). Sigmund Freud. Pisma SpoÅ‚eczne. Warszawa: Wydawnictwo KR, 1998. HJELMSLEV , L. Resume of Theory of Language. red. i tÅ‚um. na angielski Whitfield, F., Copenhagen, 1975. HOWARTH , D. Discourse. Buckingham: The Open University Press, 2000. ______; Stavrakakis , Y. Introducing Discourse Theory and Political Analysis, In: ______.; Norval , A.; Stavrakakis , Y. (Org.). Discourse Theory and Political Analysis: Identities, Hegemonies and social Change. Manchester: Manchester University Press, 2000. IDZIAK, U. DoÅ›wiadczenie Wiary jako Margines Filozofii, unpublished Ph.D. dissertation, Institute of Philosophy and Sociology, Polish Academy of Sciences, 2008. LACAN, J. The Seminar. Book III. The Psychoses, 1955-1956, London: Routledge, 1993. _______. Ecrits. New York: Norton, 2004. Laclau, E. New Reflections on the Revolution of Our Time. London: Verso, 1990. ______. Foreword. In: ______.; Norval , A., Stavrakakis , Y. Discourse Theory and Political Analysis: Identities, Hegemonies and Social Change. Manchester: Manchester University Press, 2000. _______. Constructing Universality. In: Butler , J., Laclau , E., Å½iÅ¾ek , S. (Org.). Contingency, Hegemony, Universality: Contemporary Dialogues on the Left. London: Verso, 2000a. _______. On populist Reason. London: Verso, 2005. _______., Mouffe , C. Hegemony and Socialist Strategy: Towards a Radical Democratic Politics. London: Verso, 1985. LYOTARD , J. La Condition Postmoderne: Rapport sur le Savoir. Paris: EÂ´ ditions de Minuit, 1979. MARCHART , O. Post-Foundational Political Thought. Edinburgh: Edinburgh University Press, 2007. SAUSSURE, F. De. Kurs jÄ™zykoznawstwa ogólnego. Warszawa: Wydawnictwo KR, 2002. SMITH , A. New Right Discourse on Race and Sexuality: Britain, 1968-1990, Cambridge: Cambridge University Press, 1994. ______. Laclau and Mouffe: The Radical Democratic Imaginary. New York; Routledge, 1998. STAVRAKAKIS , Y. Lacan and Political. London; New York: Routledge, 1999. Å½IÅ½EK , S. The Sublime Object of Ideology. London: Verso, 1989. ______. Enjoy your Symptom!: Jacques Lacan in Hollywood and Out. New York: Routledge, 1992. ______. The Ticklish Subject: The Absent Centre of Political Ontology. London: Verso, 1999. ______. Class Struggle or Postmodernism? Yeas Please! In: Butler , J.; Laclau , E.; Å½IÅ½EK , S. (Org.). Contingency, Hegemony, Universality: Contemporary Dialogues on the Left, London: Verso, 2000. ______. Holding the Place. In: Butler , J.; Laclau , E.; Å½iÅ¾ek , S. (Org.). Contingency, Hegemony, Universality: Contemporary Dialogues on the Left, London: Verso, 2000a. ______. PrzekleÅ„stwo fantazji. WrocÅ‚aw: Wydawnictwo Uniwersytetu WrocÅ‚awskiego, 2001. Data de Registro: 09/09/2010 Data de aceite: 20/10/2010